Does Search-Facilitating Technology Improve the Transparency of Financial Reporting? - Hodge, Frank D.; Kennedy, Jane Jollineau; Maines, Laureen A. (The Accounting Review, 2004)
XBRL (eXtensible Business Reporting Language) is an emerging technology that facilitates directed searches and simultaneous presentation of related financial statement and footnote information. We investigate whether using an XBRL-enhanced search engine helps nonprofessional financial statement users acquire and integrate related financial information when making an investment decision. We conduct our investigation in the context of recognition versus disclosure of stock option compensation. Our results reveal that many users do not access the technology, but those who do use it are better able to acquire and integrate information. Specifically, we find that when stock option accounting varies between firms, the use of an XBRL-enhanced search engine increases the likelihood that individuals acquire information about stock option compensation disclosed in the footnotes. We also find that XBRL helps individuals integrate the implications of this information, resulting in different investment decisions between individuals who use and do not use the search engine. Our results suggest that search-facilitating technologies, such as XBRL, aid financial statement users by improving the transparency of firms' financial statement information and managers' choices for reporting that information. Our results also reveal that wide publicity about the benefits of using search-facilitating technology may be needed to induce financial statement users to access the technology.